Factors Related to Nutritional Status among Preschool Children in Three Southern Border Provinces - Thapchan, Pramote; Namprom, Nethong; Chotibang, Jutamas (Princess of Naradhiwas University Journal, 2025)
Nutritional status among preschool children is an indicator of both their general health and the fundamental elements necessary for healthy growth. The objectives of this study were to: 1) examine the state of nutritional status among preschool children in three southern border provinces; and 2) investigate relationship between caregiver and child characteristics and nutritional status among preschool children in three southern border provinces. Samples were 96 caregivers of preschool children. Data were collected between January and May, 2024 with validated instruments comprised of: 1) a questionnaire for the personal information of preschool children and caregiver; 2) a record form for the nutritional status of preschool children; 3) a questionnaire for the consuming behavior of preschool children; 4) a measurement of the caregiver's knowledge regarding the nutritional status of preschool children; 5) a questionnaire for the preparation of food for preschool children; and 6) a questionnaire regarding the caregiver's attitude toward consuming. The reliability index values of these instruments were 0.80, 0.90, 0.80, and 0.82. Data were analyzed by using descriptive statistics and point biserial correlation coefficients. The results found that 64.6% of preschool children had normal nutritional status. Consuming food behavior of children, caregiver’s nutritional status knowledge, and caregivers' food preparation behavior had statistically significant positive correlations with children's nutritional status (rpb =.378, p < .01; rpb = .226, rpb = .203, p < .05). However, there was a statistically significant negative association between the caregiver's attitude regarding consumption and the children's nutritional status. (rpb = -.207, p < .05). It is necessary to encourage the caregiver's food consuming behavior, provide health education regarding nutritional status to the caregiver, encourage proper food preparation behaviors for the children, and encourage a positive attitude toward caregiver consumption to achieve normal nutritional status for preschool children.